Effect of multiple spawning on female reproductive output and offspring quality in a freshwater caridean shrimp with direct development. Issue 1 (19th January 2018) - Marciano, Agustina; Tropea, Carolina; López Greco, Laura S.
Abstract: The decline with age in components of fitness is variable among different taxa and includes changes in fertility and brood quality. In this study, we selected individuals of Neocaridina davidi, a freshwater shrimp with direct development, to analyze juvenile quality and female reproductive performance over successive spawnings, both of which are correlated with female age. Given the high costs of reproduction in species with direct development, we hypothesized that female reproductive performance and juvenile quality decrease in later spawns. Two experiments were performed. In Experiment 1, we evaluated the reproductive performance of females of N. davidi and the quality of juveniles (through a food restriction test) over the first six successive spawnings. In Experiment 2, we analyzed the lipid and protein contents in juveniles from the third, fourth, and fifth spawns, after feeding them daily or starving them for 8 d or 12 d after hatching. Female mortality was observed throughout Experiment 1, along with a decrease in the proportion of ovigerous females over successive spawns. However, the interval between spawnings and the number and size of newly hatched juveniles were similar among spawns. Moreover, females that spawned many times had a reproductive efficiency similar to those that spawned few times, as evidenced by a similar percentage of broods successfully hatched and a similar percentage of broods with more than 28 juveniles among all spawns. Overall, these results may indicate a partial effect of multiple spawning on female reproductive performance. Growth, survival, and biochemical composition of food‐restricted juveniles showed similar or even higher values in later spawns as compared to the first spawns. This is, to our knowledge, the first empirical demonstration in a decapod crustacean with direct development that, although the percentage of ovigerous females decreases over time, other reproductive variables and juvenile performance do not decline in successive spawnings, at least for the initial six consecutive spawns.